2017
DOI: 10.1186/s12911-017-0436-2
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ support for health information exchange: a literature review and classification of key factors

Abstract: BackgroundLiterature indicates that one of the most important factors affecting the widespread adoption of Health Information Exchange (HIE) is patient support and endorsement. In order to reap all the expected benefits of HIE, patients’ acceptance of technology is a challenge that is not fully studied. There are a few studies which have focused on requirements of electronic medical information exchange from consumers’ views and expectations. This study is aimed at reviewing the literature to articulate factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…Zealand and South Korea and concluded that in order to enhance the adoption of HIE, policy makers should emphasize the HIE bene ts to patients, and address their concerns [13]. Importantly, our present results indicated that positive attitudes towards HIE predicted more intention to use the system.…”
Section: Discussionsupporting
confidence: 44%
“…Zealand and South Korea and concluded that in order to enhance the adoption of HIE, policy makers should emphasize the HIE bene ts to patients, and address their concerns [13]. Importantly, our present results indicated that positive attitudes towards HIE predicted more intention to use the system.…”
Section: Discussionsupporting
confidence: 44%
“…Existing literature identified three overarching themes into which barriers and enablers of digital technology uptake were categorised. These three themes were broadly: service delivery to consumers [2, [16][17][18][19][20][21]; technology facilitation by staff members [2, 13,[22][23][24][25][26][27]; and strategic organisational factors [1-3, 18, 22, 24, 28-30]. The barriers and enablers identified were dependent on the purpose and objectives of each study.…”
Section: Methodsmentioning
confidence: 99%
“…In Australia, as elsewhere, the government has recognised that self-recording of digital clinical data can provide much needed benefits to the health system. However, the country has been relatively slow in the uptake of digital innovation in health, including technologies such as electronic health records [2,12,13]. This was evident in 2009 when the Australian Government unsuccessfully launched the Person-Controlled Electronic Health Record (PCEHR), which was later rebranded as My Health Record (MHR) in 2015 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients' comfort with the exchange of health information is affected by perceived benefits and concerns associated with the use of HIE. 13 Privacy and security concerns can be mitigated by more robust patient engagement. Notably for dialysis care, racial minorities are likely to have greater concern about sharing information with HIE.…”
Section: Patient Perceptions Of Hiementioning
confidence: 99%